Cu(OTf)(2) or Et3N-catalyzed three-component condensation of aldehydes, amines and cyanides: a high yielding synthesis of alpha-aminonitriles - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
Copper(II) triflate or Et3N have been found to catalyze, under ambient conditions, the addition of a cyanide anion, such as trimethylsilyl cyanide or acetone cyanohydrin, onto in situ generated imines, furnishing alpha-aminonitriles in excellent yields. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; aminonitriles; multicomponent reactions; organocatalyst; Strecker reaction